Preparation of jet fuel range hydrocarbons by catalytic transformation of bio-oil derived from fast pyrolysis of straw stalk. (15th June 2015) - Wang, Jicong; Bi, Peiyan; Zhang, Yajing; Xue, He; Jiang, Peiwen; Wu, Xiaoping; Liu, Junxu; Wang, Tiejun; Li, Quanxin
Abstract: The growing demand of commercial jet fuels, in combination with the strict environmental legislations, has led to immense interest in developing aviation biofuels. This work demonstrated that the bio-oil derived from fast pyrolysis of straw stalk was able to be converted into the jet and diesel fuel range hydrocarbons by a designed transformation route. This transformation included three reaction steps: (i) the catalytic cracking of bio-oil into low-carbon aromatics and light olefins, (ii) the synthesis of C8 –C15 aromatic hydrocarbons by the alkylation of low-carbon aromatics with light olefins, and (iii) the production of C8 –C15 cyclic alkanes by the hydrogenation of C8 –C15 aromatics. It was also demonstrated that the production of the desired C8 –C15 aromatics with a high selectivity of 88.4% was achieved by the low temperature alkylation reactions of the bio-oil-derived aromatics using the ionic liquid of [bmim]Cl–2AlCl3 (1-butyl-3-methylimidazolium chloroaluminate). The synthetic biofuels basically met the main technical specifications of jet fuels based on the combustion heat, viscosity, freeze point and other characteristics of fuels. Graphical abstract: A new approach for the production of C8 –C15 hydrocarbon biofuels in the jet and diesel fuel range from straw stalk derived bio-oil through the catalytic cracking of bio-oil into low carbon aromatics and light olefins followed by the low temperature alkylation of low carbon aromatics. Highlights: A novel transformation of bio-oil into jet range hydrocarbons was demonstrated. Synthesis of C8–C15 aromatic hydrocarbons was achieved by alkylation reaction. Synthesis of C8–C15 cyclic alkanes was carried out by hydrogenation of aromatics. Synthetic biofuels using bio-oil basically met main requirements of jet fuels.